Implementation of Two Stay Stray cooperative Learning (TSTS) to Improve Activity and Leraning Outcomes at SMP Negeri 12 Poleang, Indonesia - Wati La Una (Journal of Teaching and Education, 2023)
PTSTS cooperative learning needs to be integrated with the teacher as a learning facilitator in terms of group guidance because it can increase student activity and learning outcomes. The purposes of this research are (1) to describe the implementation of Two Stay Two Stray (TSTS) learning combined with group coaching in increasing the activity and learning outcomes of students at SMP Negeri 12 Poleang Barat, and increasing the learning activity of students at SMP Negeri 12 Poleang Barat through learning Two Stay Two Stray (TSTS) combined with group guidance.This research is a classroom action research conducted in two cycles. Each cycle consists of planning, action implementation, action observation, and reflection stages. The data collected is student learning activeness and student learning outcomes. The data was obtained from the results of (1) observations of students' active learning by teachers and colleagues, and (2) written test scores at the end of the cycle.The results showed that (1) the average value of student learning activity increased from 59.67 in cycle I to 84.94 in cycle II, (2) the average student learning outcomes increased from 67.18 in cycle I to 81.32 in cycle II , (3) student learning mastery increased 54.84% in cycle I to 70.97% in cycle II. These results indicate that the Two Stay Two Stray (TSTS) learning method combined with group coaching can increase student learning activity by 25.27 and student learning outcomes by 14.14. Based on the results of the data analysis, it can be concluded that the activity and learning outcomes of SMP Negeri 12 Poleang Barat students increased with the application of the Two Stay Two Stray (TSTS) learning method combined with group mentoring.